(3EOGQI GdCQHGM s - (3GdehQdj(B, (3UdGM YHO GdfHjs ((3YeGfs (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjYs, 2022)
(3jgJe gPG GdcJGH HOQGSI XGgQI EOGQI GdCQHGM, hgj YedjI GdJdGYH HGdJbGQjQ GdeGdjI dJMbjb CgOGa eYjfI(B. (3jJfGhd GdcJGH CSHGH gPg GdXGgQI, hCSGdjHgG, hBKGQgG GdSdHjI Ydi GdeSJKeQjf hGdGbJUGO(B. (3ceG jSJYQV GdcJGH GdCOhGJ hGdBdjGJ GdJj jecf GSJNOGegG ddMO ef gPg GdeeGQSGJ, eKd eYGjjQ GdeMGSHI, hOhQ GdeObbjf, hGdbhGfjf hGdCfXeI(B. (3jgOa GdcJGH Edi JSdjW GdVhA Ydi CgejI GdTaGajI hGdfRGgI aj GdEYOGO GdJbGQjQ GdeGdjI, hMeGjI eUGdM GdeSJKeQjf(B.s
Keywords: (3GdEOGQI GdeGdjI (B- (3EOGQI GdCQHGMs